الأثر الجيومورفولوجي لسد وادي زارت في مرتفعات نفوسة -ليبيا - أبو حربة, الصديق مولود (مجلة شمال إفريقيا للنشر العلمي, 2025)
Keywords: Géologie – Djebel Nefousa

الخصائص الطبوغرافية والجيومورفولوجية للجبل الغربي في ليبيا:دراسة تحليلية مدعمة بالبيانات المكانية - سعيد الحاج, زعيمة (المجلة الأفروآسيوية للبحث العلمي, 2025)
Keywords: Géologie – Djebel Nefousa

A Field Seminar Guidebook To the Geology of Jabal Nafusa, NW Libya Part 1. The Field Guide - El-Hawat, Ahmed; Sbeta, Ali (Jāmiʿat Binġāzī, 2025)
The authors designed and developed this field guidebook and associated posters for field seminars they organised and led in Jabal Nafusa from 2005 to 2009. The aim was to introduce geoscientists working for the petroleum industry to the Mesozoic geology of Jabal Nafusa, of the Jifarah arch, NW Libya.
Keywords: Géologie – Djebel Nefousa

تقييم جودة مياه الينابيع المائية في بلدية جادو، جبل نفوسة (ليبيا) - أبومنجي, زكريا محمد; القحماصي, مريم المزوغي; أبوسنينة, إبتسام أحمد (المجلة الليبية للعلوم, 2024)
Keywords: Géologie – Djebel Nefousa

Aterians in Libya - Garcea, Elena (Sessions générales et posters, section 15, préhistoire en Afrique : actes du XIVème congrès UISPP, Université de Liège, Belgique, 2 - 8 septembre 2001, 2006)
Le but de cet article est de démontrer l'existence d'horizons atériens chronologiquement,echnologiquement et typologiquement différents, qui représentent divers groupes culturels adaptés àconditions de milieu variées dans la Libye septentrionale et méridionale. Bien que certaines techniques et outillages communs appairassent sur un territoire étendu, ils sont séparés par de dizaines de millénaires. Il est probable que les populations atériennese sont organisées socialement de manière isolée. Un tel système pourrait expliquer la longue durée des traditions technologiques du MSA ancien à I'Atérien nord-african tardif et pourrait justifier leur diffirsion à un rythme très lent sur ce vaste territoire
Keywords: Géologie – Djebel Nefousa

A Preliminary Account to the Mesozoic Succession of Jabal Nefusah, NW Libya - Abdulsamad, Esam O. (مجلة الجامعي, 2003)
Keywords: Géologie – Djebel Nefousa

The Ghirian tertiary volcanic province of Tripolitania, Libya - Almond, D. C.; Busrewil, M. T.; Wadsworth, W. J. (Geological Journal, 2007)
Keywords: Géologie – Djebel Nefousa

An Early Cretaceous vertebrate assemblage from the Cabao Formation of NW Libya - Le Loeuff, Jean; Métais, Eddy; Dutheil, Didier B.; Rubino, Jean Loup; Buffetaut, Eric; Lafont, François; Cavin, Lionel; Moreau, Fabrice; Tong, Haiyan; Blanpied, Christian; Sbeta, Ali (Geological Magazine, 2010)
Fossil vertebrates from the Cabao Formation discovered in the area of Nalut in northwestern Libya include the hybodont shark Priohybodus, the crocodilian Sarcosuchus, an abelisaurid, a baryonichine spinosaurid and a large sauropod with spatulate teeth. The Cabao Formation may be Hauterivian to Barremian in age, although an earlier Berriasian to Valanginian age cannot be excluded. Its dinosaur assemblage is reminiscent of that of the El Rhaz and Tiouraren formations of Niger and strongly differs from both the Cenomanian assemblages of Morocco and Egypt and the Late Aptian to Albian fauna of Tunisia. Fossil vertebrates may be an important tool to establish the stratigraphical framework of the poorly dated Early Cretaceous continental deposits of Africa.
Keywords: Géologie – Djebel Nefousa

Biomarker Characteristics of Potential Source Rocks in the Jabal Nafusah Area, Nw Libya: Petroleum Systems Significance - Abohajar, A.; Littke, R.; Schwarzbauer, J.; Weniger, P.; Boote, D. R. D. (Journal of Petroleum Geology, 2015)
Keywords: Géologie – Djebel Nefousa

New insights on the relative sea level change during Holocene along the coasts of Tunisia and western Libya from archaeological and geomorphological markers - Anzidei, M.; Antonioli, F.; Lambeck, K.; Benini, A.; Soussi, M.; Lakhdar, R. (Quaternary International, 2011)
New data of sea level changes for the Mediterranean region along the coasts of northern Africa are presented. Data are inferred from archaeological sites of Punic-Roman age located along the coast of Tunisia, between Tunis and Jerba island and along the western coast of Libya, between Sabratha and Leptis Magna. Data are based on precise measures of presently submerged archaeological markers that are good indicators of past sea-level elevation. Nineteen selected archaeological sites were studied in Tunisia and four in Libya, all aged between ∼2.0 and ∼1.5 ka BP. The functional elevations of significant archaeological markers were measured with respect to the sea level at the time of measurements, applying corrections for tide and atmospheric pressure values. The functional elevations of specific architectural parts of the sites were interpreted, related to sea level at the time of their construction providing data on the relative changes between land and sea. Observations were compared against sea level change predictions derived from the glacio-hydro-isostatic model associated with the Last Glacial cycle. The results indicate that local relative sea level change along the coast of Tunisia and Libya, has increased 0.2 ÷ 0.5 m since the last ∼2 ka. Besides minor vertical tectonic movements of the land, the observed changes are produced by eustatic and glacio-hydro-isostatic variations acting in the Mediterranean basin since the end of the last glacial maximum.
Keywords: Géologie – Djebel Nefousa